Draft genome sequence of Fusarium oxysporum f. sp. cubense tropical race 4 from Peru, obtained by nanopore and illumina hybrid assembly - Leiva, Ana M. (2022)
Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4) is the causal agent of Fusarium wilt, a major threat to the banana industry worldwide. Here, we report the genome of a Foc TR4 strain from Peru, sequenced using a combination of Illumina and Oxford Nanopore Technologies.